Economic Impact of Smart Grids Implementation on PRE Distribuce - Haburová, Petra; Hnilica, Jiří, 1976-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2010)
The goal of this thesis is to assess the impact of the smart grids implementation on PRE Distribuce, a third largest electricity distributor in the Czech Republic. The first part of the thesis presents an overview of the current energy value chain, including the division of tasks and responsibilities. Following this is the definition of the smart grid, its drivers, benefits and key barriers of its implementation. The analytical part provides a scenario analysis of the smart grid roll-out, where the first scenario assumed implementation of all technologies and components within five years and the second scenario assumes implementation in line with the depreciation of traditional components. Furthermore, the cash flow impact and NPV of the project under both scenarios is provided.
Vedoucí práce: Jiří Hnilica
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: international Management [obor dipl. práce]; diplomové práce; master's theses